2016
DOI: 10.1136/annrheumdis-2016-209785
|View full text |Cite
|
Sign up to set email alerts
|

Disease activity trajectories in early axial spondyloarthritis: results from the DESIR cohort

Abstract: NCT01648907.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 36 publications
4
26
0
4
Order By: Relevance
“…The prospective study DEvenir des Spondyloarthrites Indifférenciées Récentes (DESIR) examined trajectories of disease and factors associated with them. The study noted that white-collar work was associated with the trajectory "persistent inactive" disease 24 . Ramiro, et al 25 reported in a longitudinal analysis of 136 patients that the relationship between disease activity and radiographic progression was significantly and independently modified by job type.…”
Section: Discussionmentioning
confidence: 98%
“…The prospective study DEvenir des Spondyloarthrites Indifférenciées Récentes (DESIR) examined trajectories of disease and factors associated with them. The study noted that white-collar work was associated with the trajectory "persistent inactive" disease 24 . Ramiro, et al 25 reported in a longitudinal analysis of 136 patients that the relationship between disease activity and radiographic progression was significantly and independently modified by job type.…”
Section: Discussionmentioning
confidence: 98%
“…The five revealed disease impact trajectories and their characterisations are largely consistent with the reported disease activity trajectories by Moltó et al . 17 For example, the largest proportion of females, highest BASDAI-scores and BASFI-scores can be found in the trajectory very high impact (t5)/persistently very high disease activity. Conversely, younger patients in combination with prescription of TNF-α-inhibitors characterise the trajectory high impact with major improvement (t3)/changing disease activity.…”
Section: Discussionmentioning
confidence: 98%
“…To gain such understanding, Moltó et al evaluated in a French cohort of patients with early axSpA the presence of potential latent subgroups with respect to disease activity during a 3-year follow-up period. 17 Five disease activity trajectories were observed: (1) persistent moderate disease activity; (2) persistent inactive disease; (3) changing disease activity; (4) persistent high disease activity; (5) persistent very high disease activity. Interestingly, in their study, a relation between the disease activity trajectories and the level of HRQoL at baseline was established.…”
Section: Introductionmentioning
confidence: 98%
“…In addition, the mean values of ASDAS (baseline 2.5, 1 yr 2.0) and PCS (baseline 28.4, 1 yr 36.9) in our cohort are comparable to other axSpA cohorts. For example, in the Devenir des Spondyloarthrites Indifférenciées Récentes (DESIR) cohort, patients with early axSpA (symptom duration < 3 yrs) had a mean ASDAS of 2.6 and PCS of 41 23 , and in the Herne 24 and Swiss Clinical Quality Management cohorts 25 (nonradiographic axSpA with a symptom duration > 5 yrs), the mean ASDAS ranged from 2.8 to 3.0 and PCS from 20 to 42, respectively. The ESPERANZA cohort has also found an association between the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) and the Ankylosing Spondylitis Quality of Life (ASQoL) questionnaire 26 .…”
Section: The Association Found Between Disease Activity Andmentioning
confidence: 99%